2007
DOI: 10.1364/ol.32.002357
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the center intensity of first- and second-order Laguerre-Gaussian beams with linear and circular polarization

Abstract: The vectorial Debye integral shows that tightly focused Laguerre-Gaussian (LG) beams have a residual intensity at the focal point for linear polarization, for a topological charge of m=1 and 2. We measured the shapes of linearly and circularly polarized LG beams and found that a central intensity appeared at m=1 and 2 for linear and right-handed circular polarization, however, it is completely canceled for left-handed circular polarization. In general, when the orbital angular momentum of the LG beam is parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 10 publications
3
42
1
Order By: Relevance
“…4. This is consistent with the behavior of the LG beams focused tightly by a high numerical aperture objective lens [12][13][14]. In other words, the change in R s due to the circular polarization direction of the LG beams is additional evidence for proper trapping on the bright rings of the focused LG beams.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…4. This is consistent with the behavior of the LG beams focused tightly by a high numerical aperture objective lens [12][13][14]. In other words, the change in R s due to the circular polarization direction of the LG beams is additional evidence for proper trapping on the bright rings of the focused LG beams.…”
supporting
confidence: 83%
“…Hence, the polarization of the trapping light is expected to be independent of the objects' revolution; i.e., J rÀpol =J lÀpol should become unity.This deviation in the experimental results from the above perspective also relates to the polarization-dependent deformation of a tightly focused LGbeam pattern [12][13][14]. Here, non-paraxial solutions of the Helmholtz equation [13][14][15] are suitable for discussing the angular-momentum properties of tightly focused circular- symmetric LG beams.…”
mentioning
confidence: 98%
“…Regarding the magnitude of the fields near r = 0 Zurita-Sánchez et al [30] have shown that, for the strongly focused azimuthally- polarized beam they studied, the magnetic interaction overcomes the electric interaction near the phase singularity; recently, their findings have been corroborated by the theoretical study of Klimov et al [49] in the case of focused Laguerre-Gaussian beams. Finally, in their research on highly-focused TL beams, Monteiro et al [63], Iketaki et al [59] and Klimov et al [49] report that interesting effects only occur when ℓ = 1, 2 and σ = −1. The overall similarities are no coincidence, for the vector potential Eq.…”
Section: Figmentioning
confidence: 97%
“…Standard fiber optic technologies can then be used for positioning the NSOM fiber and measuring the signal coupled into the fiber tip. Once the tip is protected by the fiber optic ferrule, this method offers better repeatability and is less time consuming to implement than the normal method which uses the light scattered off a nano-particle or a fluorescent bead for imaging the focal spot [14,16]. Figure 5(a) shows a 2 μm × 2 μm image of the focal spot by x-y scan of the NSOM fiber tip.…”
Section: Methodsmentioning
confidence: 99%
“…The vortex phase plate (VPP) plus the subsequent quarter-wave plate shaped the beam that upon focusing by the apochromatic microscope objective with high numerical aperture (0.9), the beam cross-section exhibits a doughnut shape central dark region appropriate for achieving lateral superresolution. The central dark region is due to the cancellation of the z-component of the electric field at the focal plane as described in [14] using the formula in [15]. Since the spatial resolution increases with depletion power [16], ideally, one would like to make use of the maximum depletion power available.…”
Section: Optical Setupmentioning
confidence: 99%